Total thoracoscopic ablation in patients with atrial fibrillation and left ventricular dysfunctionCentral MessagePerspective - Hye Ree Kim, MD; Dong-Seop Jeong, MD, PhD; Hee-Jin Kwon, MD; Seung-Jung Park, MD, PhD; Kyoung-Min Park, MD, PhD; June Soo Kim, MD, PhD; Young Keun On, MD, PhD (JTCVS Techniques)
Objective: To evaluate the effectiveness and safety of totally thoracoscopic ablation (TTA) in patients with left ventricular (LV) dysfunction for treatment of atrial fibrillation (AF) refractory to antiarrhythmic drug (AAD) therapy. Methods: Between January 2012 and December 2018, 31 patients underwent TTA with drug-refractory AF and preoperative left ventricular ejection fraction (LVEF) <50% were included. Of the 31 patients, 8 received additional catheter ablation with an electrophysiologic study within 3 months after TTA. The rhythm outcome was obtained by 12-lead electrocardiography or 24-hour Holter monitoring. Results: The patient cohort had a mean age of 54.9 ± 9.0 years and consisted of 51.6% with persistent AF (n = 16), 45.2% with long-standing persistent AF (n = 14), and 3.2% with paroxysmal AF (n = 1). No patients died during the follow-up period. Compared with baseline, mean postoperative LVEF at 3 months (interquartile range [IQR], 2-6 months) increased significantly (from 39.7 ± 6.1% to 53.6 ± 9.3%; P < .001). At 25 months (IQR, 14-45 months), LVEF was sustained or further improved (from 39.7 ± 6.1% to 58.1 ± 7.5%; P < .001). The rate of sinus rhythm state was 93.5% (29 of 31), and freedom from arrhythmias off AADs after the final procedure was 61.3% (19 of 31) at a median follow-up of 32 months (IQR, 24-54 months). Conclusions: TTA is a safe and effective procedure that improves LV function and restores sinus rhythm in AF patients with LV dysfunction.